Model of Organizational Commitment of the Head of Vocational High School in Medan North Sumatera - Purba, Sukarman; Revida, Erika (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study is to determine the Fixed Model or Theoretical Model of Organizational Commitment that can describe the structure of the causal relationship between exogenous variables with endogenous variables Organizational Commitment of Head of Vocational School in Medan City. This research was conducted in 2019 with a total sample of 106 using Kreijcie tables. Data were analyzed by path analysis after meeting the analysis requirements tet, namely the Normality and Linerity test. The research findings indicate Organizational Commitment of Had of Vocational High School are directly affected by organizational culture, academic supervision knowledge, and job satisfaction. Thus, a theoretical model or fixed model was found that illustrates the structure of the causal relationship between organizational culture variables, academic supervision knowledge, job satisfaction, and organizational commitment of head of vocational high schools in Medan City. To increase the head’s organizational commitment, organizational culture, knowledge of academic supervision, and job satisfaction must be included in the strategic planning of human resource development at the Vocational High School in Medan City, but still consider other variables that influence further organizational commitment research.